2022
DOI: 10.1038/s41467-022-34780-x
|View full text |Cite
|
Sign up to set email alerts
|

Path sampling of recurrent neural networks by incorporating known physics

Abstract: Recurrent neural networks have seen widespread use in modeling dynamical systems in varied domains such as weather prediction, text prediction and several others. Often one wishes to supplement the experimentally observed dynamics with prior knowledge or intuition about the system. While the recurrent nature of these networks allows them to model arbitrarily long memories in the time series used in training, it makes it harder to impose prior knowledge or intuition through generic constraints. In this work, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…Using the principle of variational inference implemented through deep neural networks and a predictive information bottleneck concept, a recently introduced framework leverages short MD simulations to estimate the reaction coordinates and perform iterative biased simulations that can subsequently enhance exploration of conformational landscapes and reliable inference of the associated thermodynamic and kinetic characteristics of the system. , Moreover, AI-based State Predictive Information Bottleneck (SPIB) approach can reliably learn a reaction coordinate via a deep neural network even from short and under-sampled trajectories . Further developments of these concepts produced a path sampling approach that integrates generic thermodynamic or kinetic constraints into long short-term memory (LSTM) networks to accurately learn time series such as MD trajectories for systems from different application domains . Going forward, the developments of these integrative biophysical approaches that leverage AI and ML tools to represent physics-based thermodynamic and kinetic drivers of efficient sampling in the form of neural networks would have significant implications for “autonomous” mapping of conformational landscapes, monitoring of allosteric changes, and detection of functional allosteric states.…”
Section: Expanding the Horizons Of Experiment-guided Molecular Simula...mentioning
confidence: 99%
See 1 more Smart Citation
“…Using the principle of variational inference implemented through deep neural networks and a predictive information bottleneck concept, a recently introduced framework leverages short MD simulations to estimate the reaction coordinates and perform iterative biased simulations that can subsequently enhance exploration of conformational landscapes and reliable inference of the associated thermodynamic and kinetic characteristics of the system. , Moreover, AI-based State Predictive Information Bottleneck (SPIB) approach can reliably learn a reaction coordinate via a deep neural network even from short and under-sampled trajectories . Further developments of these concepts produced a path sampling approach that integrates generic thermodynamic or kinetic constraints into long short-term memory (LSTM) networks to accurately learn time series such as MD trajectories for systems from different application domains . Going forward, the developments of these integrative biophysical approaches that leverage AI and ML tools to represent physics-based thermodynamic and kinetic drivers of efficient sampling in the form of neural networks would have significant implications for “autonomous” mapping of conformational landscapes, monitoring of allosteric changes, and detection of functional allosteric states.…”
Section: Expanding the Horizons Of Experiment-guided Molecular Simula...mentioning
confidence: 99%
“…93 Further developments of these concepts produced a path sampling approach that integrates generic thermodynamic or kinetic constraints into long shortterm memory (LSTM) networks to accurately learn time series such as MD trajectories for systems from different application domains. 94 Going forward, the developments of these integrative biophysical approaches that leverage AI and ML tools to represent physics-based thermodynamic and kinetic drivers of efficient sampling in the form of neural networks would have significant implications for "autonomous" mapping of conformational landscapes, monitoring of allosteric changes, and detection of functional allosteric states. MSM approaches are powerful tools for exploring long-time dynamic changes underlying the function of many allosterically regulated proteins, allowing for detailed network maps of functional states on the conformational landscape and quantitative analysis of the effect of perturbations on the thermodynamics and kinetics of allosteric transitions.…”
Section: Experiment-guided Molecular Simulations For Studies Of Prote...mentioning
confidence: 99%
“…More recently, it was shown that subsampling the LSTM-predicted paths subject to physical constraints based on the maximum caliber principle and retraining the LSTM model on this subset of paths could lead to improved quality in obtaining thermodynamic and kinetic properties of biomolecular systems. 116 As the recurrent neural network approach was originally developed for one-dimensional natural language processing, we expect that this LSTM approach alone may perform optimally on one-dimensional data. 117 Nevertheless, the LSTM architecture can be incorporated into a larger framework to perform complex multidimensional tasks.…”
Section: Deep Learning Recurrent Neural Network Modelsmentioning
confidence: 99%
“…More recently, it was shown that subsampling the LSTMpredicted paths subject to physical constraints based on the Maximum Caliber principle and re-training the LSTM model on this subset of paths could lead to improved quality in obtaining thermodynamic and kinetic properties of biomolecular systems. 116 As the recurrent neural network approach was originally developed for one-dimensional natural language processing, we expect that this LSTM approach alone may perform optimally on one-dimensional data. 117 Nevertheless, the LSTM architecture can be incorporated into a larger framework to perform complex multidimensional tasks.…”
Section: E Deep Learning Recurrent Neural Network Modelsmentioning
confidence: 99%